2012
DOI: 10.1155/2012/371414
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Llama Bacterial Artificial Chromosome Library with Approximately 9-Fold Genome Equivalent Coverage

Abstract: The Ilama is an important agricultural livestock in much of South America. The llama is increasing in popularity in the United States as a companion animal. Little work has been done to improve llama production using modern technology. A paucity of information is available regarding the llama genome. We report the construction of a llama bacterial artificial chromosome (BAC) library of about 196,224 clones in the vector pECBAC1. Using flow cytometry and bovine, human, mouse, and chicken as controls, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…BAC end sequences (BESs) and marker not only provide a snapshot of the sequence composition of the genome of the species of interest but also aid in genome assembly [ 3 , 18 ], chromosome walking [ 19 ], identifying genetic markers [ 20 ], and mapping genes to specific loci using fluorescence in situ hybridization (FISH) technology [ 21 ]. In this study, 916 BESs were obtained with an average high quality base-pair number of 586 bp, and 72 new SSRs were found in 66 BESs.…”
Section: Discussionmentioning
confidence: 99%
“…BAC end sequences (BESs) and marker not only provide a snapshot of the sequence composition of the genome of the species of interest but also aid in genome assembly [ 3 , 18 ], chromosome walking [ 19 ], identifying genetic markers [ 20 ], and mapping genes to specific loci using fluorescence in situ hybridization (FISH) technology [ 21 ]. In this study, 916 BESs were obtained with an average high quality base-pair number of 586 bp, and 72 new SSRs were found in 66 BESs.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 15 years, BAC libraries have been extensively used in physical mapping and complete eukaryote genome sequencing [19–22]. Previous studies have shown that a clonal coverage of 6.0–8.0 genome equivalents was sufficient for the development of a genome-wide physical map of approximately 95% genome coverage.…”
Section: Discussionmentioning
confidence: 99%